Investigation into alternative cooling methods for achieving environmentally friendly machining process - Ginting, Y.; Boswell, Brian; Biswas, W.; Islam, Mohammad Nazrul (Elsevier, 2015)
© 2015 The Authors. Published by Elsevier B.V. The machining of metals has traditionally involved the use of large quantities of water and oils for dissipating the cutting tool temperature, improving the surface finish of parts and increasing tool life. Invariably, the cutting fluid has become contaminated with use, has required being environmentally disposed and has accounted for approximately 17% of the total production cost of parts. A Streamline Life Cycle Assessment (SLCA) of machining of parts has been carried out to investigate the environmental and energy saving benefits associated with the replacement of traditional cooling method, with Minimum Quantities of Liquid (MQL) combined with cold compressed air.